Ferromagnetism in metal oxide systems: interfaces, dopants, and defects - Thakare, Vishal P.; Game, Onkar S.; Ogale, Satishchandra B. (Journal of Materials Chemistry C, 2013)
Ferromagnetism in metal oxide systems has always attracted scientific attention in view of the intriguing and interesting interplay of spin, charge, orbital and lattice degrees of freedom that such systems display. This trend appears to be continuing with enhanced focus on interface systems, multiferroics, diluted magnetic semiconducting oxides (DMSOs) and nanomaterial magnetism. Newer techniques are being applied to bring out materials issues that are critical to the precise understanding of the origin of magnetism in certain cases. Interest is also beginning to grow in exploring application potential of some such systems. In this article we review the developments in this field by late 2011 and 2012.

Promising field electron emission performance of vertically aligned one dimensional (1D) brookite (beta) TiO2 nanorods - Devan, Rupesh S.; Ma, Yuan-Ron; More, Mahendra A.; Khare, Ruchita T.; Antad, Vivek V.; Patil, Ranjit A.; Thakare, Vishal P.; Dhayal, Rajendra S.; Schmidt-Mende, Lukas (RSC Advances, 2016)
We evidence field-electron emission (FE) studies on the large-area array of one-dimensional (1D) brookite (beta) TiO2 nanorods. The pure 1D beta-TiO2 nanorods of 10 nm width and 760 nm long were synthesized on Si substrate utilizing hot-filament metal vapor deposition technique. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis evidenced the beta-TiO2 nanorods to be composed of orthorhombic crystals in brookite (beta) phase. X-ray photoemission spectroscopy (XPS) revealed the formation of pure stoichiometric (i.e. 1 : 1.98) 1D TiO2 nanorods. The values of turn-on field, required to draw current density of 10 mA cm(-2), was observed 3.9 V mu m(-1) for pristine 1D beta-TiO2 nanorods emitters, which were found significantly lower than doped/undoped 1D TiO2 nanostructures (i.e. nanotubes, nanowires, nanorods) based field emitters. The enhanced FE behavior of the TiO2/Si emitter can be attributed to modulation of electronic properties due to the high aspect ratio of vertically aligned TiO2 nanorods. Furthermore, the orthodox emission situation of pristine TiO2/Si emitters exhibit good emission stability and reveal their potentials as promising FE material.

Nano-heteroarchitectures of two-dimensional MoS 2 @ one-dimensional brookite TiO 2 nanorods: prominent electron emitters for displays - Devan, Rupesh S.; Thakare, Vishal P.; Antad, Vivek V.; Chikate, Parameshwar R.; Khare, Ruchita T.; More, Mahendra; Dhayal, Rajendra S.; Patil, Shankar I.; Ma, Yuan-Ron; Schmidt-Mende, Lukas (ACS Omega, 2017)
We report comparative field electron emission (FE) studies on a large-area array of two-dimensional MoS2-coated @ one-dimensional (1D) brookite (β) TiO2 nanorods synthesized on Si substrate utilizing hot-filament metal vapor deposition technique and pulsed laser deposition method, independently. The 10 nm wide and 760 nm long 1D β-TiO2 nanorods were coated with MoS2 layers of thickness ∼4 (±2), 20 (±3), and 40 (±3) nm. The turn-on field (Eon) of 2.5 V/μm required to a draw current density of 10 μA/cm² observed for MoS2-coated 1D β-TiO2 nanorods emitters is significantly lower than that of doped/undoped 1D TiO2 nanostructures, pristine MoS2 sheets, MoS2@SnO2, and TiO2@MoS2 heterostructure-based field emitters. The orthodoxy test confirms the viability of the field emission measurements, specifically field enhancement factor (βFE) of the MoS2@TiO2/Si emitters. The enhanced FE behavior of the MoS2@TiO2/Si emitter can be attributed to the modulation of the electronic properties due to heterostructure and interface effects, in addition to the high aspect ratio of the vertically aligned TiO2 nanorods. Furthermore, these MoS2@TiO2/Si emitters exhibit better emission stability. The results obtained herein suggest that the heteroarchitecture of MoS2@β-TiO2 nanorods holds the potential for their applications in FE-based nanoelectronic devices such as displays and electron sources. Moreover, the strategy employed here to enhance the FE behavior via rational design of heteroarchitecture structure can be further extended to improve other functionalities of various nanomaterials.